Age and Temperature of Globular-Open Star Clusters Case Study : M3 M35 and M67 - Thassana, Chewa; Maithong, Wiraporn (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2017)
In this work, the age and the temperature of the globular cluster M3 and the open clusters M37 and M67 were observed by CCD Photometer via a 0.5-meter Rithchey-Chertien Reflecting Telescope at Regional Observatory for the Public Nakhon Ratchasima, Thailand ; images were obtained of the cluster stars in B and V photometric filter. The magnitude of the cluster stars were analyzed by Iris and Aperture Photometry Tool (ATP) program. The age and temperature of M3, M35 and M67 clusters were calculated by the apparent magnitude and color index (B-V) of the Hertzsprung-Russell diagram . Our results shown that the both open cluster M35 and M67 were found to lie at a distance of 2,700 light years (832pc) from the Earth. In addition, the M35 is approximately 110 million years old and the temperature in range of 7,000 -13,000K. Meanwhile M67 is roughly 3.11 billion years old, the temperature is about 4,400K to 6,400K. However, we determined that the globular cluster M3 is approximately 11.1 billion years old and located 34,000 light years (10,420pc) away from the Earth, while temperature is around 3,600 -6,800K.